Effect of the coaches' leadership style perceived by athletes on team cohesion among elite Brazilian futsal players - Nascimento Junior, José Roberto Andrade; Vissoci, João Ricardo Nickenig; Codonhato, Renan; Fortes, Leonardo de Sousa; de Oliveira, Daniel Vicentini; Oliveira, Leonardo Pestillo; Nascimento, Juarez Vieira; Fiorese, Lenamar (Cuadernos de Psicología del Deporte, 2018)
This study investigated the effect of the coach leadership style as perceived by athletes on team cohesion among elite futsal athletes. Participants were 120 athletes from the top-8 teams participating in the Paraná’s state Professional League 2013. Instruments used were the Leadership in Sport Scale and the Group Environment Questionnaire. For data analysis, Confirmatory Factor Analysis and Structural Equation Modelling were conducted, as well as Latent Profile Analysis. Results showed significant relationships between leadership style and both social (10%) and task cohesion (31%); in addition, the coach leadership style perceived by athletes characterized as democratic and based on social support, reinforcement and training-instruction influenced positively task cohesion (FL=0.55) and moderately social cohesion (FL=0.31). It is concluded that, for the futsal from the state of Parana, the coach’s leadership style based on democratic, reinforcement, social support and training-instruction behaviours is determinant to the development of task cohesion, however, does not have the same strong influence in social cohesion.